A Case Study of the 6A Tourism Components in Enhancing Tourists' Visit Intention to Cibinong Botanical Garden, West Java - Monica Marshellya; Vishnuvardhana S. Soeprapto (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Cibinong Botanical Garden is a nature-based and educational tourism destination with considerable potential; however, challenges related to its supporting tourism components may affect tourists’ intention to visit. This study aims to analyze the role of the 6A tourism components, namely attraction, accessibility, amenities, activities, ancillary services, and available packages, in enhancing tourists’ intention to visit, identify the most influential component, and formulate strategies for destination development. This study employed a qualitative case study approach at Cibinong Botanical Garden, West Java. Data were collected through observation, in-depth interviews with destination managers, marketing staff, and tourists, and documentation, and were analyzed using qualitative data analysis techniques. The findings reveal that the six tourism components function complementarily in shaping tourists’ intention to visit. Among these components, attraction emerged as the most influential factor, primarily through the presence of iconic lakes, endemic flora collections, extensive green open spaces, and the destination’s educational tourism concept. Activities and available packages also enrich the overall visitor experience by providing more diverse and structured tourism opportunities. However, amenities, accessibility, and ancillary services require further improvement, particularly regarding public toilet quality, informational signage, pedestrian pathways, visitor information services, and the digitalization of tourism services. This study concludes that integrated and sustainable management of the 6A tourism components is a strategic approach to enhancing destination quality, improving visitor satisfaction, and encouraging both initial and repeat visits to Cibinong Botanical Garden. The findings contribute to destination management and sustainable tourism studies by emphasizing the importance of component-based tourism development in strengthening the competitiveness of nature-based educational destinations.